\[ f(x) = q(x) d(x) + r(x) \]

When \(d(x) \) is a polynomial with no repeated roots, Prasun has stated how we could determine \(r(x) \) using the Remainder-Factor Theorem.

How should we deal with the case when \(d(x)\) has repeated roots?

What is the remainder when \( x^{10} \) is divided by \( (x-1) ^2 \)?

What is the remainder when \( x^{10} \) is divided by \( (x-1) ^2 (x+1) \)?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestDifferentiate throughout and evaluate the expression at the value of the repeated root.

Log in to reply

That's one possible approach. However, as \(d(x) \) gets complicated, you could run into various issues. E.g. how would you evaluate the 2 given questions?

Is there another simpler way?

Hint:How can we apply partial fractions cover up rule to repeated roots?Log in to reply

\(f(x) = x^n\)

\(f(1) = 1\)

\(f(x) = (x - 1)Q(x) + 1\)

\(f'(x) = Q(x) + (x - 1)Q'(x)\)

\(f'(x) = nx^{n-1}\)

\(f'(1) = n\)

\(Q(1) = n\)

\(Q(x) = (x - 1)q(x) + n\)

\(f(x) = (x - 1)((x - 1)q(x) + n)) + 1\)

\(f(x) = (x - 1)^{2}q(x) + nx - n + 1\)

\(f(x) = (x - 1)^{2}(x + 1)q_1(x) + a(x - 1)^{2} + nx - n + 1\)

\(f(x) = x^{10}\)

\(f(-1) = 1\)

\(4a - 19 = 1\)

\(a = 5\)

Log in to reply

Yes, that is the right approach. More generally,

What does this remind you of?Hint:What is the remainder when \( f(x) \) is divided by \( (x-a) ^3 \)@Sudeep Salgia @Prasun Biswas The above is a useful way to remember how to find the remainder when divided by a linear power. It forms the linkage between remainders of a polynomial, and how the polynomial looks like at a point.

Log in to reply

Log in to reply

Log in to reply

Wait, IM SO CLOSE I MIGHT HAVE FIGURED IT OUT

Log in to reply

Please avoid typing in all capital letters, as that is considered rude on the internet.

Log in to reply

\(x^n = ((x - a) + a)^n\)

Log in to reply

What is the general solution, and why?

Find the "one-line" explanation for it.

Log in to reply

\((( x - a) + a)^n = \sum_{i=0}^n nC_i (x - a)^{n - i} a^i\)

Log in to reply

What is a one-line explanation for the answer?

Log in to reply

Log in to reply